Semantic Issues and Their Resolution in Linguistic Studies - Nur Hidayanti, Eka; Novita Harianja, Chorry; Sari, Rulia; Asrahapiza; Balqis, Ratu; Hana Pebriana, Putri (The Future of Education Journal, 2025)
Semantic studies in linguistics are a fundamental aspect of understanding the structure of meaning and language interpretation. However, in practice, various semantic issues arise, such as ambiguity, meaning deviation, semantic shifts, and the use of metaphors—particularly in the increasingly evolving digital communication landscape. This article provides an in-depth analysis of these forms of semantic problems and presents scientific approaches to address them. Through a literature review of various relevant sources and studies, it is found that semantic issues are dynamic and contextual in nature; thus, their resolution requires an interdisciplinary approach involving pragmatics and sociolinguistics. Contextual understanding of semantics is key to bridging meaning gaps in language interaction.